DIRECT TRAINING ON SIKO NOODLES MARKETING STRATEGIES IN LHOKSEUMAWE CITY TO INCREASE COMPETITIVE STRENGTH IN THE MARKET - Amru Usman; Tarmizi Abbas; Nur Faliza; Rico Nur Ilham; Muttaqien; Irada Sinta (RADJA PUBLIKA, 2024)
The aim of this research is to determine the marketing strategy of Mie Siko MSMEs, especially the marketing mix. This research uses qualitative methods, namely case studies that produce descriptive data expressed in words. The data collection technique for this research is that the author directly visited Mie Siko MSMEs to interview the owners of MIE SIKO MSMEs. The research results show that the marketing strategy used by Mie Siko MSMEs is 4P marketing which consists of product, price, place and promotion. The product strategy is defining the logo, creating the brand, and the label. The pricing strategy offers relatively affordable prices. The location strategy is a strategic location and can be accessed by many people. The promotional strategy provides free toppings for 10 purchases. Even though Mie Siko MSMEs are facing the problem of declining sales, they are still looking for solutions by preserving cash, maximizing social media as a promotional tool and creating market place accounts. In conclusion, the marketing strategy for Mie Siko MSMEs is quite good, but considering the large number of MSMEs in Lhokseumawe, it is best for the owner to continue increasing their promotion on social media.